2020
DOI: 10.1021/acs.nanolett.0c02005
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable Perovskite Supercrystals via Oil-in-Oil Templating

Abstract: Inorganic perovskites display an enticing foreground for their wide range of optoelectronic applications. Recently, supercrystals (SCs) of inorganic perovskite nanocrystals (NCs) have been reported to possess highly ordered structure as well as novel collective optical properties, opening new opportunities for efficient films. Here, we report the large-scale assembly control of spherical, cubic, and hexagonal SCs of inorganic perovskite NCs through templating by oil-in-oil emulsions. We show that an interplay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 33 publications
(77 reference statements)
0
44
0
Order By: Relevance
“… 12 , 68 , 69 Recently, a carrier solvent–surfactant pair suitable for dispersing perovskite NC colloidal droplets (in toluene) was developed, namely, fluorinated solvents FC-40 or HFE-750 and fluorinated surfactant 008-FS, yielding single-component perovskite supraparticles. 70 Here, we extend the method to binary SLs with perovskite NCs ( Figure 16 ). Supraparticles with b-ABO 3 -type structures can be obtained from the emulsions of 8.6 nm CsPbBr 3 and 18.6 nm NaGdF 4 NCs ( Figure 16 b).…”
Section: Results and Discussionmentioning
confidence: 99%
“… 12 , 68 , 69 Recently, a carrier solvent–surfactant pair suitable for dispersing perovskite NC colloidal droplets (in toluene) was developed, namely, fluorinated solvents FC-40 or HFE-750 and fluorinated surfactant 008-FS, yielding single-component perovskite supraparticles. 70 Here, we extend the method to binary SLs with perovskite NCs ( Figure 16 ). Supraparticles with b-ABO 3 -type structures can be obtained from the emulsions of 8.6 nm CsPbBr 3 and 18.6 nm NaGdF 4 NCs ( Figure 16 b).…”
Section: Results and Discussionmentioning
confidence: 99%
“…This process likely is also largely responsible for the decrease of the photoluminescence quantum yield from 50.8 to 28.2% upon the formation of SBs that was observed in our previous work. 17 …”
Section: Resultsmentioning
confidence: 99%
“…A 12 or 60 μL aliquot of 008-FS in FC-40 (5 wt %) was injected into 588 or 540 μL of neat FC-40, forming 0.1 or 2 wt % 008-FS in FC-40, respectively. 17 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eq. ( 4) with z = 0, Tang et al [35] found that N ≈ 2.65 for freshly synthesized and N ≈ 1.8 for aged samples, respectively.…”
Section: Governing Equationsmentioning
confidence: 98%